APC gene 3′UTR SNPs and interactions with environmental factors are correlated with risk of colorectal cancer in Chinese Han population. Issue 3 (20th March 2020) - Ying, Rongbiao; Wei, Zhiping; Mei, Yuxian; Chen, Shasha; Zhu, Liming
Abstract: Objective: To study the correlation between adenomatous polyposis coli ( APC ) gene 3′ untranslated region (UTR) single nucleotide polymorphisms (SNPs) and their interactions with environmental factors and the risk of colorectal cancer (CRC) in a Chinese Han population. Methods: Genotypes of APC gene 3′UTR rs1804197, rs41116, rs448475, and rs397768 loci in 340 Chinese Han patients with CRC and 340 healthy controls were analyzed. All patients with CRC were analyzed for progression-free survival (PFS) during a 3-year follow-up. Results: The risk of CRC in subjects carrying the APC gene rs1804197 A allele was 2.95-times higher than for the C allele carriers. The interactions of the rs1804197 SNP with body mass index (BMI) and smoking were associated with the risk of CRC. The risk of CRC in the APC gene rs397768 G allele carriers was 1.68-times higher than in the A allele carriers. The interaction between the rs397768 locus SNP and gender was also associated with the risk of CRC. The 3-year PFS of patients with APC gene rs1804197 AA genotype, CA genotype, and CC genotype CRC decreased in this order, with significant difference. In addition, the 3-year PFS of rs397768 locus GG genotype, AG genotype, and AA genotype CRC patients decreased in this order, and the difference was significant. Conclusion: The rs1804197 locus in the 3′UTR region of the APC gene and its interactions with BMI and smoking are associated with the risk of CRC in a Chinese Han population. In addition, the interaction between rs397768 locus SNP and gender is related to the risk of CRC.